دورالتأمين مقام العاقلة في دفع الديات الناتجة من الحوادث، دراسة تحليلية = The status of insurance as an alternative to aqilah for diyat payments pertaining to road accidents - Muhammad Husni, Ahmad; Omar, Anwar Fakhri; Alias, Muhammad Nazir; Samuri, Mohd. Al Adib (Institut Islam Hadhari, Universiti Kebangsaan Malaysia, 2013)
يعد التأمين من أهم القضايا المعاصرة والمستجدة لدى المسلمين، لما يحمل بين طياته مفاهيم عديدة لا يجد المرء نفسه إلاّ الوقوف عنده، ويعد دراسته دراسة شرعية وعملية تطبيقية، لمعرفة ما إن كانت هذه القضية التي شغلت بال المسلمين منذ أكثر من ستين عاماً من خلال اللقاءات الدولية والعلمية مطابقة لمقاصد الشريعة الإسلامية وأسسها،فموضوع دفع الدية من قبل شركات التأمين المعاصرة يعتبر واحد من أهم القضايا الفقهية المستجدة في الوقت الحاضر. حيث درج العرف بين الناس عند المطالبة بالدية، بالاقتصار على مبلغ التعويض الذي تدفعه شركات التأمين المعاصرة، خاصة فيما ينتج عن حوادث السيارات وما هي البدائل التي قدموها عبر هذه المجامع عند عدم وجود العاقلة أو بيت مال للمسلمين ومإذا عن عدم تمكن العاقلة نفسها بالدفع لظروف ما أو ومدى حاجة المجتمع المسلم إلى مثل هذا النوع من العقود، فنهجت الدراسة إلى المنهج الاستقرائي التحليلي لجمع آراء الفقهاء والباحثين وأدلتهم وحججهم حول الموضوع، والنصوص المتعلقة به محاولاً تحليلها تحليلاً أصوليا وفقهيا بما يناسب واقعنا المعاصر ومقصد الشريعة. و إلى المنهج التطبيقي أي دراسة الموضوع دراسة تطبيقية وميدانية. فخلصت الدراسة على أن لابد للشركات التجارية أن تقوم مقام العاقلة في دفع الدية عن الجاني المخطئ المستأمن فيها، وأن لا يفرق بين الدية والتعويض من حيث المطالبة والاختصاص. *********************************************************************************Di sesetengah negara Islam, kes-kes kemalangan jalan raya dikategorikan sebagai kesalahan kecederaan dan membunuh tidak sengaja. Undang-undang negara tersebut memperuntukkan pihak yang terkilan untuk menuntut bayaran diyat daripada pesalah yang akan dibayar oleh aqilah iaitu ahli keluarga lelaki. Persoalan yang timbul, sejauhmana sistem aqilah dapat digantikan oleh institusi insurans sebagai pembayar diyat kepada mangsa atau keluarganya? Objektif artikel ini dibuat ialah untuk melihat sejauh mana institusi insurans berpotensi untuk menggantikan peranan aqilah dalam membayar diyat bagi kes-kes kemalangan jalan raya. Perkara ini penting untuk dikaji kerana institusi insurans adalah institusi kewangan yang lebih efektif dalam melindungi para pencarumnya dan berpotensi untuk menggantikan sistem aqilah yang terlalu terhad kapasiti kewangannya. Kajian mendapati bahawa institusi insurans berpotensi untuk menggantikan peranan sistem aqilah dalam pembayaran diyat kepada mangsa atau keluarganya yang terlibat dalam kes kemalangan jalan raya. Institusi insurans mempunyai persamaan dengan sistem aqilah dari aspek konsep asas, peranan dan juga operasi dalam mencapai matlamat sistem aqilah. *********************************************************************************In some Islamic countries, traffic accidents are categorised as unintentional harm or fatality cases. The laws of these countries allow for the aggrieved party to demand diyat (compensation for the loss suffered) from the offender that may be paid by their aqilah (in its original context, means community or tribe), or male family members. The question that then arises is to what extent can the aqilah be replaced by insurance agencies as the payer of diyat to the victim(s) or their respected families? The objective of this article is to determine this extent, specifically with regards to traffic accidents. This is an issue of great significance because insurance agencies are better equipped and more effective at providing coverage and protection to their policyholders, and as such have the potential to replace the aqilah system in situations where the financial means for such a payment is not present. Studies have shown that insurance agencies do indeed possess the potential to replace the aqilah system in the capacity of diyat compensation to victim(s) or their families, especially in the case of road accidents. It should be pointed out that insurance agencies possess inherent similarities to the aqilah system, particularly in relation to its basic concept, role and execution in achieving the same goals.